α‐synuclein suppresses microglial autophagy and promotes neurodegeneration in a mouse model of Parkinson’s disease - Tu, Hai‐Yue; Yuan, Bao‐Shi; Hou, Xiao‐Ou; Zhang, Xiao‐Jun; Pei, Chong‐Shuang; Ma, Ya‐Ting; Yang, Ya‐Ping; Fan, Yi; Qin, Zheng‐Hong; Liu, Chun‐Feng; Hu, Li‐Fang (Aging cell, 2021)
The cell‐to‐cell transfer of α‐synuclein (α‐Syn) greatly contributes to Parkinson's disease (PD) pathogenesis and underlies the spread of α‐Syn pathology. During this process, extracellular α‐Syn can activate microglia and neuroinflammation, which plays an important role in PD. However, the effect of extracellular α‐Syn on microglia autophagy is poorly understood. In the present study, we reported that extracellular α‐Syn inhibited the autophagy initiation, as indicated by LC3‐II reduction and p62 protein elevation in BV2 and cultured primary microglia. The in vitro findings were verified in microglia‐enriched population isolated from α‐Syn‐overexpressing mice induced by adeno‐associated virus (AAV2/9)‐encoded wildtype human α‐Syn injection into the substantia nigra (SN). Mechanistically, α‐Syn led to microglial autophagic impairment through activating toll‐like receptor 4 (Tlr4) and its downstream p38 and Akt‐mTOR signaling because Tlr4 knockout and inhibition of p38, Akt as well as mTOR prevented α‐Syn‐induced autophagy inhibition. Moreover, inhibition of Akt reversed the mTOR activation but failed to affect p38 phosphorylation triggered by α‐Syn. Functionally, the in vivo evidence showed that lysozyme 2 Cre (Lyz2cre)‐mediated depletion of autophagy‐related gene 5 (Atg5) in microglia aggravated the neuroinflammation and dopaminergic neuron losses in the SN and exacerbated the locomotor deficit in α‐Syn‐overexpressing mice. Taken together, the results suggest that extracellular α‐Syn, via Tlr4‐dependent p38 and Akt‐mTOR signaling cascades, disrupts microglial autophagy activity which synergistically contributes to neuroinflammation and PD development. Autophagy‐dependent and independent machinery synergistically contribute to hα‐Syn‐caused neuroinflammation in PD. The basal autophagy activity restricts microglia inflammation. Extracellular hα‐Syn interacts with and activates Tlr4, resulting in inflammatory responses, as well as autophagy suppression in microglia via Tlr4‐dependent p38 and Akt/mTOR signaling cascades. This impairs the inhibitory effect of autophagy on inflammation, and thus aggravating hα‐Syn‐induced inflammatory responses.